A new error estimate of a finite difference scheme for a fractional transport-advection equation with zero order term - Allaoua Mehri; Hakima Bouhadjera; Mohammed S. Abdo; Najla Alghamdi; Sahar Ahmed Idris (Alexandria Engineering Journal)
In this work, we propose a finite difference scheme for Caputo’s fractional derivative transport equation in time and space, with a zero-order term. A new error estimation of the approximate solution has been demonstrated. By introducing an approximation of the Caputo derivative, we proved that the convergence is of order 2-α in time, and 2-β in space, for 0<α;β<1. Results of conditional stability and convergence of the numerical method are discussed. Finally a numerical implementation was presented to show the conformity between the theoretical and numerical approach of the finite difference scheme.